Motivasi Mahasiswa terhadap Aktivitas Olahraga pada Sore Hari di Sekitar Area Taman Sutera Universitas Negeri Semarang - Abdulaziz, Moch Fahmi; Dharmawan, Dhimas Bagus; Putri, Dwi Tiga (Journal of Physical Education Health and Sport, 2016)
This study aims to determine the motivation of students to sports activities in the afternoon around the area Taman Sutera Semarang State University. The method used in the study was a survey with quantitative approach and data analysis used is descriptive percentage. The results showed that colleger motivation to do sports activities due to the physiological needs of the average values obtained by 84.27%, 87.61% safety needs, social needs 79.27%, 59.83% appreciation needs and self-actualization needs 77, 55%, while the reasons colleger choose Unnes Sutera park area on the sporting at afternoon as the potential of facilitating the environment enough to engage in sports activities such as safe, comfortable and healthy gives the feel of the availability of O2 (oxygen) and a green and clean environment. Based on the results of this study concluded that the motivation of colleger on the sporting in the Unnes Sutera park as significant because of the need for security and physiological needs, meaning that provide comfort colleger in doing sports activities and can be recommended for Unnes to improve and develop the open space special exercise around the Unnes Sutera park to provide optimal contribution in improving the culture of sports.